2002
DOI: 10.1136/sti.78.3.201
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of HSV-1 and HSV-2 infection in the general French population

Abstract: Background: In spite of the large prevalence and growing incidence of herpes simplex infection (HSV-1 and HSV-2), relatively few large serological surveys are available worldwide and it is still difficult compare frequencies of HSV contaminations in various countries. We present the results of HERPIMAX, the first epidemiological inquiry on HSV prevalence in the general French population. Methods: Of a cohort of 12 735 presumed healthy adult volunteers included in the prospective study SU.VI.MAX, designed to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
40
7
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 13 publications
13
40
7
5
Order By: Relevance
“…This agrees with Malkin et al 27 who found a higher HSV-1 infection in people of lower education level in France. Rezaei-Chaparpordi et al 25 also observed an increase in prevalence of HSV antibodies with a decrease in level of education.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…This agrees with Malkin et al 27 who found a higher HSV-1 infection in people of lower education level in France. Rezaei-Chaparpordi et al 25 also observed an increase in prevalence of HSV antibodies with a decrease in level of education.…”
supporting
confidence: 82%
“…This suggests that these groups of females were at a greater danger of acquiring HSV 27 for instance, HSV gotten in the course of pregnancy is connected with spontaneous abortion 27 which occur highest in first trimesters, and risk of neonatal transmission with highest risk occurring at third trimester. The study also showed a seronegativity of 0.6% among the pregnant women tested and is therefore at high risk and vulnerable to suffering a primary genital herpes.…”
mentioning
confidence: 99%
“…HSV-2 antibody prevalence has been reported to be 17% in the French general adult population (4) and to range from 4 to 24% in other, similar, European populations (5, 8). Our HSV-2 antibody prevalence appeared to be statistically significantly higher than that previously reported by Malkin et al (4) in the French general population (17.2% of 12,735 subjects), even after the values were adjusted according to age or gender (P Ͻ 0.001). Taken together, our findings showed high rates of HSV-2 antibody prevalence in two cohorts of French HIV-1-infected outpatients, suggesting that HSV-2 infection may be markedly associated with HIV-1 infection in France.…”
contrasting
confidence: 53%
“…[42] Adolescents are known to be at increased risk of acquiring HSV infections because of fewer protective antibodies (Agarwal and Gupta, 2000). [43] Similar results are reported by another study (Malkin et al 2002). [44] The presence of the rubella IgM antibodies was found in 1 (out of 2 suspected cases) female in the age group of 21 -40 years.…”
Section: Discussionsupporting
confidence: 80%